Study of DMSA (99mTc-dimercaptosuccinic acid) scan disorders in children 1-12 years with first acute pyelonephritis and its association with vesicoureteral reflux - Vafaie, Majid; Zare-noghabi, Javad; Bahri, Hadiseh (International Journal of Research in Medical Sciences, 2018)
Background: Acute pyelonephritis and vesicoureteral reflux are one of the main causes of renal scarring in children, which can lead to serious complications such as hypertension and chronic renal failure. The aim of this study was to evaluate the scan disorders in children aged 1-12 years with acute pyelonephritis and its relation with ureteral bladder reflux. Methods: This retrospective cross-sectional descriptive study was conducted on all patients who had been diagnosed with febrile UTI for 4 years (2012-2015) in Ardebil's Children's Hospital. Information about 99mTc-DMSA scan and ultrasonography and cystoyurethrography of patients were extracted from the files and then analyzed by statistical methods inSPSS.19. Results: 148 children (9 boys and 139 girls) with a range of 1 to 12 years old (mean age of 52.34±4.34 months) were included in the study. Of these, 123 patients were subjected to cystoyurethrography after a negative urine culture. A 99mTc-DMSA scan report in the acute phase of the disease was abnormal in 80.4% of the children. VCUG and RNC tests were performed in 123 patients, in 70 (57%) normal cases, and in 53 cases (43%) of urinary reflux. The incidence of reflux with abnormal 99mTc-DMSA scan was 42%. There was no significant correlation between the prevalence of reflux in patients with abnormal 99mTc-DMSA scan in two groups of 1-4 years old and more than 4 years old. No significant difference was found in patients with abnormal scan in responding to treatment and comparing fever after admission in patients with normal 99mTc-DMSA. Conclusions: The results indicate high prevalence of reflux in patients with acute pyelonephritis. Due to the high sensitivity of the scan to detect pyelonephritis and, Pyelonephritis.